2011
DOI: 10.1080/17290376.2011.9724981
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychological inoculation on cognitive barriers against condom use in women with HIV: A controlled pilot study

Abstract: Journal des Aspects Sociaux du VIH/SIDA 27 Article Original RésuméDes études antérieures ont montré que dans les tentatives pour prévenir le VIH, les efforts d' éducation sanitaire modifiaient peu la fréquence d'utilisation d'un préservatif. C' est peut-être parce que l' éducation ne parvient pas à cibler les obstacles liés au changement de comportement. La présente étude pilote contrôlée a tenté de savoir si l'inoculation psychologique (IP) réduit ou non ces obstacles dans l'utilisation de préservatifs mascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Similar to Banas and Rains (2010) findings, Parker et al (2012) found that inoculation treatment extended to protection against untreated or novel issues. It is also the case that from the developing country of Nigerian, there is confirmation of the greater efficacy of psychological inoculation treatment to reduce cognitive barriers to condom use compared to heath education in a pilot quasi-experimental study conducted with a small sample of HIV-positive Nigerian women (Olley et al, 2011). These authors also found that women who received the health education control treatment tended to slightly improve on the outcome variables.…”
Section: Intersectionality Theory and Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar to Banas and Rains (2010) findings, Parker et al (2012) found that inoculation treatment extended to protection against untreated or novel issues. It is also the case that from the developing country of Nigerian, there is confirmation of the greater efficacy of psychological inoculation treatment to reduce cognitive barriers to condom use compared to heath education in a pilot quasi-experimental study conducted with a small sample of HIV-positive Nigerian women (Olley et al, 2011). These authors also found that women who received the health education control treatment tended to slightly improve on the outcome variables.…”
Section: Intersectionality Theory and Researchmentioning
confidence: 93%
“…These authors also found that women who received the health education control treatment tended to slightly improve on the outcome variables. Hence, there is emerging research evidence which suggests that as a preventative measure, the combination of health education with psychological inoculation is likely to decrease risky behaviors among individuals at risk for HIV (Olley et al, 2011). …”
Section: Intersectionality Theory and Researchmentioning
confidence: 99%
“…Moreover, past studies show that self-efficacy, an important component within the Theory of Planned Behavior, may affect intention to perform behavioral changes (Williams, Kessler, & Williams, 2015). However, self-efficacy was not assessed in the studies presented here, an outcome which was found to be increased by the PI in the previous study mentioned above (Olley et al, 2011).…”
Section: Limitationsmentioning
confidence: 58%
“…While a recent meta-analysis found that behavioral interventions were effective in increasing condom use, such interventions required a counselor (Scott-Sheldon, Huedo-Medina, Warren, Johnson, & Carey, 2011). In addition, the PI pilot study of Olley et al (2011) relied on therapist contact. These reduce the applicability to en-masse interventions for trying to achieve wide spread HIV prevention globally.…”
Section: Introductionmentioning
confidence: 99%
“…Once such emerging intervention is psychological inoculation (PI), which exposes participants to challenging sentences which reflect their social pressures and cognitive barriers, they must reject. Indeed, one pilot-controlled study found PI to have a stronger effect on condom use barriers than education alone (Olley, Abbas, & Gidron, 2011 ).…”
Section: Discussionmentioning
confidence: 99%